Yellow fever outbreak in Brazil: the puzzle of rapid viral spread and challenges for immunisation - Possas, Cristina (Mem Inst Oswaldo Cruz, 2018)
We discuss the complex eco-social factors involved in the puzzle of the unexpected rapid viral spread in the ongoing Brazilian yellow fever (YF) outbreak, which has increased the reurbanisation risk of a disease without urban cases in Brazil since 1942. Indeed, this rapid spatial viral dissemination to the Southeast and South regions, now circulating in the Atlantic Forest fragments close to peri-urban areas of the main Brazilian megalopolises (São Paulo and Rio de Janeiro) has led to an exponential increase in the number of yellow fever cases. In less than 18 months, 1,833 confirmed cases and 578 deaths were recorded most of them reported in the Southeast region (99,9%). Large epizooties in monkeys and other non-human primates (NHPs) were communicated in the country with 732 YF virus (YFV) laboratory confirmed events only in the 2017/2018 monitoring period. We also discuss the peculiarities and similarities of the current outbreak when compared with previous great epidemics, examining several hypotheses to explain the recent unexpected acceleration of epizootic waves in the sylvatic cycle of the YFV together with the role of human, NHPs and mosquito mobility with respect to viral spread. We conclude that the most feasible hypothesis to explain this rapidity would be related to human behavior combined with ecological changes that promoted a significant increase in mosquito and NHP densities and their contacts with humans. We emphasize the urgent need for an adequate response to this outbreak such as extending immunisation coverage to the whole Brazilian population and developing novel strategies for immunisation of NHPs confined in selected reserve areas and zoos. Finally, we stress the urgent need to improve the quality of response in order to prevent future outbreaks and a catastrophic reurbanisation of the disease in Brazil and other South American countries. Continuous monitoring of YFV receptivity and vulnerability conditions with effective control of the urban vector Aedes aegypti and significant investments in YF vaccine production capacity and research and development for reduction of adverse effects are of the highest priority.